Pemarkah Kesantunan Linguistik Tuturan Bahasa Jepang Staf Hotel di Bali - Indah Kusumarini (LACULTOUR: Journal of Language and Cultural Tourism, 2022)
Services in the hotel industry are generally formal. The asymmetric relationship between the service buyer and the service provider has implications for the hotel's procedures in providing services to guests, such as maintaining of courtecy and polite speech. Based on the results of data analysis of conversations between Japanese guests and hotel staff in Bali, several verbal politeness markers  in hospitality services have been found, they are; modality (1) “ please”, (2) “would you please”, (3) "if you please", (4) “what”, (5) “is there”,(6) “do you please?”, (7) prefix o or go + guest object, like oheya (your room), (8) the greeting word "Okyaku sama" which means "Mr/Madam/Miss", (9) expressions in hotel services, such as (a) greeting, (b) offering help, (c) inviting, (d) apologizing, (e) thanking, (f) requesting, (g) giving advice, (h ) give attention. (i) excuse me, (j) wish good things to guests. All of them are performented in keigo (honorific language) so that based on the concept of politeness, these expressions are relatively safe, do not threaten the faces of guests or hotel staff.